PERBANDINGAN SISTEM EKONOMI ISLAM DENGAN SISTEM EKONOMI KAPITALIS DAN SOSIALIS - Syamsul Effendi (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2020)
The capitalist economic system is a system of economic organization that is characterized by private property rights to the tools of production and distribution and utilization to achieve a profit in a very comparative condition. This capitalism is the result of Adam Smith's thought, Adam Smith is a classical sect figure where the world's economic experts assess that the classical sect's thinking is the basis of a capitalist economic system. Doctrines taught by the theory of economic system capitalist, namely about the value of goods and services, the price structure, ie the price in the production area, the price in determining the consumption and price in the method of determining production. The rationale of Adam Smith's theory was able to endure until the economic depressi of 1929. At that time J. M Keyness performed and succeeded in expressing a theory that new and improved economic system can be built, Keynesian thought requires the presence of government intervention in determining economic policy, this is the beginning of the fall of the capitalist economic system. Because the economic crisis has always occurred throughout history, it is necessary an alternative economic theory. The Dicita-citakan economic theory is an economic system that is able to create justice and shared welfare, accompanied by the concept of the blessing of the world and the hereafter. This is the theory of Islamic economics that will bring justice and complete prosperity. Islamic economics is regarded as a way out to address contemporary economic issues. The source of the idea of Islamic economic system is aqidah and Islamic ideology which is the foundation of the Quranic massage and as-Sunnah. With this foundation the Islamic economy is distinctive, unique and distinct from the capitalist economic system or socialist/Communist economic system. In the capitalist economic system, economic activity is conducted solely because of the benefits and material factors, so as not to pay attention to the interests of the crowd. There is also no guarantee the perfection of this economic system even brings disaster that afflict the people. The Islamic economic system is an independent economic system and apart from other economic systems. As for the difference of Islamic economic system with other economic systems is as revealed by Suroso Imam Zadjuli in Achmad Ramzy Tadjoeddin, namely that the principle of Islamic economics is the application of basic efficiency dam benefits while preserving the natural environment. And the motive of Islamic economics is to seek good luck in the world and in the hereafter as the FIL with the path of worship in a broad sense. Islam recognizes the welfare of the individual and the social welfare of the community that complements one another instead of competing against each other, as applicable in the capitalist and socialist economic system.